Managerial competences of researchers from Nursing research groups - Greici Capellari Fabrizzio; Alacoque Lorenzini Erdmann; José Luís Guedes dos Santos; Susana Cararo Confortin; Ana Lúcia Schaefer Ferreira de Mello; Aida Maris Peres (Universidade de São Paulo, 2021)
Objective: to analyze the managerial competences of researchers from research groups linked to a Graduate Program in Nursing. Method: a cross-sectional study with researchers from Nursing research groups, which analyzed the managerial competences by means of a Scale of Managerial Competences in Research Groups containing 50 items related to people management and research results (Factor 1) and resource provisioning and people management (Factor 2), with answers 4 and 5 considered as sufficient dexterity for each competence analyzed. For data analysis, logistic regression was used. Results: of the 219 participants evaluated, the prevalence was 48.86% of sufficient dexterity for factor 1 and 32.88% of sufficient dexterity for factor 2; with 41.21% of sufficient dexterity for Managerial Competences in research groups. A significant difference was identified in the proportions of the managerial competences for schooling, age group and performance in the group (p≤0.001). There were differences in mean age, time of experience with research and participation in the research group (p≤0.001), between the participants with sufficient and insufficient dexterity for the managerial competences. Conclusion: the results obtained in this study emphasize the potential of the research groups for the development of managerial competences of Nursing researchers, especially for people management.